Gait quality and function after fampridine treatment in patients with multiple sclerosis – A prospective cohort study. (December 2022) - Thorning, Maria; Nielsen, Helle Hvilsted; Frich, Lars Henrik; Jensen, Henrik Boye; Lambertsen, Kate Lykke; Holsgaard-Larsen, Anders
Abstract: Background: Fampridine has shown to improve walking speed, motor control, and balance in patients with multiple sclerosis. However, potential fampridine-induced changes in gait quality and underlying mechanisms, evaluated by three-dimensional gait analysis, are poorly examined. The aim was to examine if two weeks of fampridine treatment would improve gait quality (using Gait Profile Score and Gait Variable Scores from three-dimensional gait analysis) and gait function (using performance-based tests, spatiotemporal parameters, and self-perceived gait function). Methods: 14 participants with multiple sclerosis were included (9 women and 5 men, age 53.6 ± 12.8 years, disease duration 21 ± 9.1 years) in this cohort study. Tests were completed prior to fampridine and after 14 (± 1) days of treatment. Three-dimensional gait analyses were completed, and kinematic measures were calculated for overall gait quality using Gait Profile Score, and for joint-specific variables, Gait Variable Scores. Gait function was assessed using spatiotemporal parameters, performance-based tests, and a patient-reported outcome measure. Student's paired t -test/Wilcoxon signed rank test were used to compare baseline and follow-up variables. Sample size calculation for Gait Profile Score required at least 9 participants. Findings: No fampridine-induced improvements in gait quality were demonstrated. For gait function, improvements were found in performance-based tests ( Timed 25-Foot Walk : −11.5%; Six Spot Step Test : −13.9%; 2-Minute Walk Test : 18.2%) and self-perceived gait function ( 12-item MS Walking Scale: –35.2%). Interpretation: Although two weeks of fampridine treatment in patients with multiple sclerosis improved gait function, there was no change in overall kinematic quality of gait. Trial registration: This work was collected as a part of a registered clinical trial (MUST): ClinicalTrials.gov NCT03847545 Highlights: Two weeks of Fampridine treatment did not improve kinematic gait quality. Gait function/performance improved following two weeks of Fampridine treatment. No Fampridine induced improvements were detected in spatiotemporal parameters. Changes in kinematic gait quality and gait function/performance did not correlate.